Peran Lingkungan Sekolah dalam Membentuk Etika Bertutur Kata Siswa - Syarifatul Insaniyah; M. Syarif; Saifuddin Saifuddin (Universitas Maritim AMNI Semarang, 2024)
This study examines the influence of the school environment on students' speaking ethics at SMA Negeri 1 Gedeg Mojokerto, considering the importance of character education in schools as a place where students spend much of their time. Using a correlational method and quantitative research type, the researcher involved 193 eleventh-grade students from a population of 425 as respondents. Data collection was carried out through a questionnaire with 38 statements that had been tested for validity and reliability. Data analysis included descriptive analysis, normality test, linearity test, as well as correlation coefficient analysis, determination coefficient analysis, and simple regression analysis for hypothesis testing. The results showed that the school environment and students' speaking ethics were in the moderate category, with average scores of 65 and 73, respectively. There is a significant influence of the school environment on students' speaking ethics, as evidenced by the t-test result (8.364) being greater than the t-table (1.97), leading to the acceptance of Ha and the rejection of Ho. Simple linear regression analysis showed a regression coefficient of 29.881, with an R square of 0.268, indicating that the school environment positively affects speaking ethics by 26.8%, while 73.2% is influenced by other factors. This study supports the theory that the school environment influences students' speaking ethics.